2012
DOI: 10.1121/1.4756927
|View full text |Cite
|
Sign up to set email alerts
|

In situ source levels of mulloway (Argyrosomus japonicus) calls

Abstract: Mulloway (Argyrosomus japonicus) in Mosman Bay, Western Australia produce three call categories associated with spawning behavior. The determination of call source levels and their contribution to overall recorded sound pressure levels is a significant step towards estimating numbers of calling fish within the detection range of a hydrophone. The source levels and ambient noise also provide significant information on the impacts anthropogenic activity may have on the detection of A. japonicus calls. An array o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…In other species, it has been shown that SL increases with size while peak frequency decreases (Connaughton et al, 2000), thus the observed differences were expected. In contrast, the maximum SELs in the larger fish were lower than the smaller fish suggesting that the pulse duration was longer (Parsons et al, 2012). This is in line with the lower peak frequencies in calls of the larger fish.…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…In other species, it has been shown that SL increases with size while peak frequency decreases (Connaughton et al, 2000), thus the observed differences were expected. In contrast, the maximum SELs in the larger fish were lower than the smaller fish suggesting that the pulse duration was longer (Parsons et al, 2012). This is in line with the lower peak frequencies in calls of the larger fish.…”
Section: Discussionsupporting
confidence: 52%
“…The remaining SL variation is not unusual in the wild. Parsons et al (2012) limits in SLs of a single A. japonicus at various ranges, while Lagardere and Mariani (2006) noted considerable differences in pressure amplitudes of consecutive pulses within single calls of Argyrosomus regius. Such variation has been noted in calls of other species as well (Nilsson, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations